Nurses’ moral suffering, burnout and turnover intentions: A two-wave study - Gherman, Mihaela-Alexandra (Nursing ethics, 2026)
Background Nurses suffered an unprecedented number of potentially morally injurious events (PMIEs) during the COVID-19 pandemic. Their long-term associations with organizational well-being remain unknown.Research aim We aimed to assess whether psychological basic need thwarting characteristic of nurses? episodic memories of PMIEs from the pandemic, either enacted (self-PMIEs) or passively witnessed (other-PMIEs), explained unique burnout and turnover intentions variance 2 years after the events.Research design We present findings of a quantitative, two-wave longitudinal study (2022, when the pandemic peaked, and 2024, post-pandemic), focusing on comparing the two waves. In 2022, participants were randomly assigned to self-report need-thwarting associated with memories of either self-PMIEs or other-PMIES (quasi-experimental design). During both waves, they filled in questionnaires for burnout, turnover intentions, work-related psychological need satisfaction and socio-demographic factors.Participants and research context Through chain-referral methods, we purposively sampled 463 Romanian nurses working in hospitals at the peak of the pandemic in 2022, with 350 remaining in 2024.Ethical considerations Ethical approval was granted by the faculty ethics committee. Participants were fully informed of the research purpose and their rights prior to both waves.Findings Linear mixed models showed that need-frustration associated with memories of self-PMIEs (assessed in 2022) significantly predicted burnout and turnover intentions in 2024. For memories of other-PMIEs, the relationships became nonsignificant in 2024.Conclusions Episodic memories of self-PMIEs continue to contribute to nurses? burnout and turnover intentions 2 years after the events. Organizational efforts for fostering positive retrospective appraisals through counseling services are needed, along with creating a safe climate where ethical misdemeanors may be disclosed and processed without fear of sanctions.